Analisis Dampak Pengumuman Dividen Terhadap Reaksi Pasar (Studi Kasus Pada Perusahaan Indeks Saham LQ45) - Melati, Rampi; Risman, Asep (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2023)
In general, investors demand diverse, precise, and high-quality data and information. Investors eagerly anticipate the announcement of dividends because the announcement of dividend distribution is a crucial factor influencing investors in their investment decisions. Market efficiency, when viewed solely from the perspective of information, is referred to as an informationally efficient market. This research aims to analyze and test whether there is a difference in abnormal returns before and after dividend announcements. The study employs the event study method on the LQ45 stock index with a research period of 11 days, namely 5 days before the announcement, at the announcement (t=0), and 5 days after the dividend announcement. Based on the results of the Paired Sample t-test hypothesis, abnormal returns before and after dividend announcements show a significance value of 0.782. Since the significance value is ≥ 0.05, H0 is accepted, indicating no difference in abnormal returns before and after dividend announcements